2023
DOI: 10.1186/s13059-023-02862-8
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism underlying redundant functions of the YTHDF proteins

Abstract: The YTH N6-methyladenosine RNA binding proteins (YTHDFs) mediate the functional effects of N6-methyladenosine (m6A) on RNA. Recently, a report proposed that all YTHDFs work redundantly to facilitate RNA decay, raising questions about the exact functions of individual YTHDFs, especially YTHDF1 and YTHDF2. We show that YTHDF1 and YTHDF2 differ in their low-complexity domains (LCDs) and exhibit different behaviors in condensate formation and subsequent physiological functions. Biologically, we also find that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…Dependence on m6A has been shown for YTHDF proteins, which promote m6A-mediated degradation in proportion to the number of m6A sites in the transcript (Boo et al, 2022; Zaccara & Jaffrey, 2020; Zou et al, 2023). In contrast, our datasuggest an m6A-independent effect of YTHDC1 in mediating the RNAPII pausing/release process, as pause release did not show a clear correlation with the presence of m6A sites despite the binding of YTHDC1 to the regulated genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Dependence on m6A has been shown for YTHDF proteins, which promote m6A-mediated degradation in proportion to the number of m6A sites in the transcript (Boo et al, 2022; Zaccara & Jaffrey, 2020; Zou et al, 2023). In contrast, our datasuggest an m6A-independent effect of YTHDC1 in mediating the RNAPII pausing/release process, as pause release did not show a clear correlation with the presence of m6A sites despite the binding of YTHDC1 to the regulated genes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study found dynamic levels of O -GlcNAc modifications appearing on YTHDF1/3 proteins, but not YTHDF2, dependent on background, indicating that they do have diverse functions [ 41 ]. Nevertheless, it is important to interpret RNA stability data from triple YTHDF1/2/3 knockdown/knockout experiments with care, as depletion of all three YTHDF proteins results in an increase in cellular P-body formation in HeLa cells, consequently leading to the global stabilisation of most mRNAs which is not strictly dependent on m 6 A [ 42 ].…”
Section: A Promotes Rna Degradationmentioning
confidence: 99%
“…This mapping identified high-scoring interactions with mRNA silencing factors such as the CCR4-NOT deadenylase complex, the exoribonuclease XRN1, and the translational repressor DDX6 14 . By contrast, Zou et al argued that YTHDF1, 2 and 3 have distinct partners using C-terminal BirA fusions, assuming that YTHDF1 is found with translation machineries such as initiation factors (eIFs), while YTHDF2 associates better with mRNA silencing factors, and YTHDF3 is in the margin between YTHDF1 and 2 17 .…”
Section: Introductionmentioning
confidence: 99%